Impact of foreign workers in oil palm plantation sector at Layang-Layang, Johor / Aleena Mohamad Amin - Mohamad Amin, Aleena (Faculty of Plantation and Agrotechnology, 2019)
The statistics of foreign workers in Malaysia are growing yearly as most employers prefer to recruit them as workforce in industry. Thus, study on the impact of foreign workers specified in oil palm plantation sector is conducted at Layang-layang area in Johor. The objectives are to evaluate the relationship of factors that influence the negative impact induced by foreign workers in plantation sector and the sub-aimed of this study is to determine the most influence factor that contribute to the negative impact induced by foreign workers in plantation. The factors are over-dependence on foreign workers, lack of interest of local workers to work in plantation and existence of illegal workers. A structured questionnaire is designed and distributed to the executive levels as respondent. The sample for this study is 70 samples using Table Krejchie and Morgan, 1970. The data collected and analyzed using Statistical Package for Social Science (SPSS) program. The data analyzed using correlation and multiple regression analysis. The descriptive analysis is included gender, job position, education level, working experiences and profile of studied place. The study shows that factors of over-dependence on foreign workers and lack of interest of local workers have weakly negative correlation. While, factor of existence of illegal workers has weak positive correlation. From the analysis tested, only factor of over-dependence on foreign workers have significant correlation coefficient where it also a major factor that contribute to the negative impact induced by foreign workers. Government should take initiative to improve technologies in plantation so that employers are not too rely on foreign labor.